Effects of sublethal dose of fipronil on neuron metabolic activity of africanized honeybees - Roat, Thaisa Cristina [UNESP]; Carvalho, Stephan M. [UNESP]; Nocelli, Roberta C. F.; Silva-Zacarin, Elaine C. M.; Palma, Mario Sergio [UNESP]; Malaspina, Osmar [UNESP] (Springer Nature, 2013)
Fipronil is a neurotoxic insecticide that inhibits the gamma-aminobutyric acid receptor and can affect gustative perception, olfactory learning, and motor activity of the honeybee Apis mellifera. This study determined the lethal dose (LD50) and the lethal concentration (LC50) for Africanized honeybee and evaluated the toxicity of a sublethal dose of fipronil on neuron metabolic activity by way of histochemical analysis using cytochrome oxidase detection in brains from worker bees of different ages. In addition, the present study investigated the recovery mechanism by discontinuing the oral exposure to fipronil. The results showed that mushroom bodies of aged Africanized honeybees are affected by fipronil, which causes changes in metabolism by increasing the respiratory activity of mitochondria. In antennal lobes, the sublethal dose of fipronil did not cause an increase in metabolic activity. The recovery experiments showed that discontinued exposure to a diet contaminated with fipronil did not lead to recovery of neural activity. Our results show that even at very low concentrations, fipronil is harmful to honeybees and can induce several types of injuries to honeybee physiology. © 2012 Springer Science+Business Media New York.
Keywords: cytochrome c oxidase; fipronil; brain; concentration (composition); dose-response relationship; ecotoxicology; honeybee; inhibition; injury; insecticide; learning; metabolism; neurology; physiology; pollution exposure; sublethal effect; acute toxicity; histochemistry; LC 50; LD 50; mitochondrion; nerve cell; nonhuman; priority journal; Apis mellifera; Apis mellifera scutellata; Apoidea; Basidiomycota